1992
DOI: 10.1029/92jd01087
|View full text |Cite
|
Sign up to set email alerts
|

Convective boundary layer budgets of moisture and sensible heat over an unstressed prairie

Abstract: Convective boundary layer budgets of sensible heat and moisture were evaluated for 2 days over the unstressed vegetation of the tallgrass Konza National Prairie during IFC 1 of the First International Satellite Land Surface Climatology Project (ISLSCP) Field Experiment (FIFE) 87. On June 1, 1987, winds were strong, while on the other day, June 4, 1987, winds were light. Data for the budgets came from morning and afternoon missions of the NCAR King Air aircraft. In addition to the budget evaluation the study ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 25 publications
(13 reference statements)
1
24
0
Order By: Relevance
“…Others have focused on the CBL turbulence structure in CBLs with wind shear at the surface (LeMone 1973;Pennel and LeMone 1974). Some of the more recent studies have specifically estimated entrainment flux ratios under conditions of broadly varying surface heating and shear (Grossman 1992;Betts et al 1992;Betts and Ball 1994;Betts and Barr 1996;Barr and Strong 1996;Davis et al 1997;Flamant et al 1997;Angevine 1999;Margulis and Entekhabi 2004), but the methods of analysis varied, and the scatter in their estimates of entrainment flux ratio as a function of entrainment zone shear indicates that other factors, not specifically addressed in those analyses, also influence the entrainment flux ratio. Some of the more recent studies have specifically estimated entrainment flux ratios under conditions of broadly varying surface heating and shear (Grossman 1992;Betts et al 1992;Betts and Ball 1994;Betts and Barr 1996;Barr and Strong 1996;Davis et al 1997;Flamant et al 1997;Angevine 1999;Margulis and Entekhabi 2004), but the methods of analysis varied, and the scatter in their estimates of entrainment flux ratio as a function of entrainment zone shear indicates that other factors, not specifically addressed in those analyses, also influence the entrainment flux ratio.…”
Section: B Existing Methods Of Estimating Shear Contribution To the mentioning
confidence: 99%
“…Others have focused on the CBL turbulence structure in CBLs with wind shear at the surface (LeMone 1973;Pennel and LeMone 1974). Some of the more recent studies have specifically estimated entrainment flux ratios under conditions of broadly varying surface heating and shear (Grossman 1992;Betts et al 1992;Betts and Ball 1994;Betts and Barr 1996;Barr and Strong 1996;Davis et al 1997;Flamant et al 1997;Angevine 1999;Margulis and Entekhabi 2004), but the methods of analysis varied, and the scatter in their estimates of entrainment flux ratio as a function of entrainment zone shear indicates that other factors, not specifically addressed in those analyses, also influence the entrainment flux ratio. Some of the more recent studies have specifically estimated entrainment flux ratios under conditions of broadly varying surface heating and shear (Grossman 1992;Betts et al 1992;Betts and Ball 1994;Betts and Barr 1996;Barr and Strong 1996;Davis et al 1997;Flamant et al 1997;Angevine 1999;Margulis and Entekhabi 2004), but the methods of analysis varied, and the scatter in their estimates of entrainment flux ratio as a function of entrainment zone shear indicates that other factors, not specifically addressed in those analyses, also influence the entrainment flux ratio.…”
Section: B Existing Methods Of Estimating Shear Contribution To the mentioning
confidence: 99%
“…The LES results reveal that the moisture fluxes decrease over time, whereas the buoyancy and CO 2 fluxes are closely clustered around a single curve. Grossman (1992), Davis et al (1997), andLeMone et al (2002) also found that the moisture exchange decreases during the daytime. This can be explained by the fact that in the morning, the ABL specific humidity decreases due to entrainment of dry air, which has a larger effect than the release of moisture at the surface.…”
mentioning
confidence: 98%
“…Estimates of ␤ based on aircraft measurements in similar conditions are similar to our LES value, but typically larger than the aircraft value. Observed estimates show large variations, ranging from 0.08 Ϯ 0.12 in Davis et al (1997) to Ϫ0.03-0.8 in Grossman (1992) and 0.6 in Vilà-Guerau de Arellano et al (2004). While in our study, we focus on one particular day, Davis et al (1997) calculated an average ␤ value from 19 days that consists of morning and afternoon flights during the Boreal Ecosystem-Atmosphere Study (BOREAS-94) campaign.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These studies all used series of radiosonde flights to determine the budget quantities. In addition, Betts et al [1992], Grossman [ 1992], and Davis et al [1997] used aircraft measurements for budget studies. Theoretical studies were made by Stull [ 1976] and Tennekes [1973] among others.…”
mentioning
confidence: 99%